2021
DOI: 10.3390/en14196438
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Spillovers and Asymmetric Spillover Effect between the Carbon Emission Trading Market, Fossil Energy Market, and New Energy Stock Market in China

Abstract: In 2020, China proposed the goal of achieving carbon emission peaks by 2030 and carbon neutrality by 2060. For China, whose energy consumption structure has long been dominated by fossil energy, carbon trading and new energy are crucial for the realization of the emission target. By establishing a connectedness network model, this paper studies the static and dynamic spillovers between the Hubei carbon trading market, new energy stock market, crude oil market, coal market, and natural gas market in China, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…There are many researches on the influence of different industries, mainly focusing on the field of energy consumption industry. Scholars have studied the positive effects of carbon trading market on fossil energy market (Nie et al, 2021;Jiang et al, 2022a), non-fossil energy industry (Liu J. Y et al, 2021) and steel industry (Duan et al, 2021).…”
Section: The Impact Of Carbon Emission Trading Policy On Macroeconomi...mentioning
confidence: 99%
See 1 more Smart Citation
“…There are many researches on the influence of different industries, mainly focusing on the field of energy consumption industry. Scholars have studied the positive effects of carbon trading market on fossil energy market (Nie et al, 2021;Jiang et al, 2022a), non-fossil energy industry (Liu J. Y et al, 2021) and steel industry (Duan et al, 2021).…”
Section: The Impact Of Carbon Emission Trading Policy On Macroeconomi...mentioning
confidence: 99%
“…It could also promote coordinated emission reductions of CO 2 and other atmospheric pollutants including nitrogen oxides (NO X ), Dust pollutants (Dust) Jiang et al, 2022b). Some other scholars found that the regional porter effect of carbon emission trading was not stimulated (Nie et al, 2021), but caused the marginal CO 2 emission reduction cost in the pilot region to fluctuate up (Duan et al, 2021).…”
Section: The Impact Of Carbon Emission Trading Policy On Macroeconomi...mentioning
confidence: 99%
“…For developed countries, technological progress reduces household energy consumption, but for industry, it will expand energy consumption. Nie et al (2021) believe that the government's expansion of R&D expenditure can alleviate enterprises' emission behavior to a certain extent. Meanwhile, ordered environmental regulation can force enterprises to reduce carbon emissions in the short term, but in the long run, it may increase enterprises' behavior of emissions theft or excess.…”
Section: Technological Innovation and Carbon Emissionsmentioning
confidence: 99%
“…E i represents the energy consumption (physical quantity), 44 represents the molecular weight of carbon dioxide, and 12 represents the molecular weight of carbon. Since carbon dioxide is mainly from fossil fuels, based on the studies of Heryadi and Hartono (2016), Bian et al (2017), andNie et al (2021), eight kinds of energy are selected: natural gas, fuel oil, diesel oil, kerosene, gasoline, crude oil, coking coal, and coal. The parameters of eight kinds of energy under formula (8) are given in Table 2…”
Section: Input-output Indicators Of Carbon Emissionsmentioning
confidence: 99%
“…In research on the volatility spillover of the carbon market, Chevallier (2009) used a variety of GARCH models to prove that the volatility of carbon prices is affected by the stock market and bond market. Zhang and Sun (2016) used DCC-TGARCH and BEKK-GARCH models to explore the spillover effect between the energy market and carbon market and found that there is a strong correlation between the coal market and the carbon market (Dou et al 2021;Yu et al 2020;Nie et al 2021). Wang and Guo (2018) and Adekoya et al (2021) used the spillover index structured by Diebold and Yilmaz (DY) to analyze the time-varying spillover effects.…”
Section: Introductionmentioning
confidence: 99%